Ovarian teratoma-associated anti-NMDAR encephalitis in a 12-year-old girl - Soe, Lwin; Myat, San Yi; Mardiana, Kipli; Woon, SY; Tin, Moe Nwe; Wan Zuraida, Wan Azemi (2020)
aspartate receptor (anti-NMDAR) is one of the most commonautoimmune encephalitis syndromes and it is a serious andpotentially fatal pathology that occurs in young women. Thiscase report describes of a pediatric patient with anti-NMDARencephalitis. A-12-year-old girl presented with abnormalbehavior for one week came to Emergency Department ofSarawak General Hospital, Malaysia. She had psychoticspectrum symptoms including suicidal tendency. She wasdiagnosed with anti-NMDAR encephalitis as positiveantibody was seen in her cerebrospinal fluid. She wastreated with Injection Immunoglobulin. She turned out tohave teratoma which was successfully removed later. Herprogress was remarkable after the surgery with theImmunoglobulin. A multi-disciplinary team involving apsychiatrist, neurologist and gynaecologist liaised withintensivist to successfully manage the case and achieve thegood outcome.